Soil Insect Diversity and Community Structure as Bioindicators in the Semi-Arid Ecosystem of Madapangga Nature Park, Indonesia - Olahairullah; Ariyansyah; Mulisa (Jurnal Penelitian Pendidikan IPA, 2026)
Soil insects play an important role in ecosystem processes, particularly in organic matter decomposition and nutrient cycling. This study aimed to analyze the composition and diversity structure of soil arthropod communities in Madapangga Nature Park, Bima Regency, West Nusa Tenggara, Indonesia. Field sampling was conducted from June to July 2024 using quadrat sampling and pitfall traps at two observation stations. A total of 629 individuals representing 15 species, 13 families, and 8 orders were collected and identified. The Shannon-Wiener diversity index showed a low-to-moderate diversity level (H′ = 1.005), indicating community imbalance due to the dominance of several taxa. Hymenoptera was the dominant order, with arthropod gracilipes comprising approximately 23% of the total collected individuals. The dominance of this invasive ant species may indicate ecological pressure or habitat disturbance within the study area. Environmental measurements showed slightly acidic soil conditions with pH ranging from 5.5–5.9 and soil temperatures ranging from 25–27°C. These abiotic conditions may influence the distribution and abundance of soil arthropod communities. The findings provide preliminary ecological data for biodiversity monitoring and conservation management in semi-arid conservation ecosystems, particularly in the Madapangga Nature Park area and similar environments in Nusa Tenggara.